A comparison of the ability of a new bispyridinium oxime--1-(4-hydroxyiminomethylpyridinium)-4-(4-carbamoylpyridinium)butane dibromide and currently used oximes to reactivate nerve agent-inhibited rat brain acetylcholinesterase by in vitro methods - Kuca, K; Kassa, J (Journal of enzyme inhibition and medicinal chemistry, 2003)
The efficacy of a new bispyridinium oxime 1-(4-hydroxyiminomethylpyridinium)-4-(4-carbamoylpyridinium)butane dibromide, called K048, and currently used oximes (pralidoxime, obidoxime, the oxime HI-6) to reactivate acetylcholinesterase inhibited by various nerve agents (sarin, tabun, cyclosarin, VX) was tested by in vitro methods. The new oxime K048 was found to be a more efficacious reactivator of nerve agent-inhibited acetylcholinesterase than pralidoxime (in the case of VX, tabun and cyclosarin), obidoxime (cyclosarin and tabun) and HI-6 (tabun) but it did not reach the efficacy of currently used oximes for the reactivation of acetylcholinesterase inhibited by sarin. Thus, the oxime K048 seems to be a relatively efficacious broad spectrum acetylcholinesterase reactivator and, therefore, it could be useful for the treatment of a nerve agent-exposed population if information about detection of the type of nerve agent is not available.
Keywords: Dose-Response Relationship, Drug; pyridinové sloučeniny; Rats; vztah mezi dávkou a účinkem léčiva; Acetylcholinesterase; In Vitro Techniques; Cholinesterase Reactivators; cholinesterasové inhibitory; acetylcholinesterasa; Cholinesterase Inhibitors; mužské pohlaví; Rats, Wistar; mozek; Oximes; techniky in vitro; krysa rodu Rattus; Pyridinium Compounds; Enzyme Activation; Brain; zvířata; Nervous System; aktivace enzymů; molekulární struktura; nervový systém; potkani Wistar; oximy; reaktivátory cholinesterasy; Male; Molecular Structure; Animals